EXPLORING THE EFFECTS OF TECHNOLOGY ON CHILD DEVELOPMENT AND EDUCATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the impact of technology on young children's cognitive, social, and emotional development. It presents evidence-based research on the positive and negative effects of technology use on child development, such as enhancing cognitive skills while decreasing social interaction. The article also discusses parental mediation and digital literacy skills as effective strategies to regulate children's screen time and promote healthy technology use